Accounting for the Growth of Real Wages of U.S. Manufacturing Production Workers since the Nineteenth Century - John H. Pencavel (Institute of Labor Economics (IZA), 2024)
Why have the real (consumption) wages of U.S. workers risen since the nineteenth century? Some economists answer that increases in real wages have followed increases in labor productivity over time. In this paper, this hypothesized association is confronted with annual observations of changes in the wages and changes in the labor productivity of U.S. manufacturing production workers from the end of the 19th century to the beginning of the 21st century. Correlates with changes in real wages in addition to productivity are considered including statutory legislation, trade unionism, and the state of the business cycle.
Keywords: J31; N31; N32; 330; real wages; labor productivity; trade unions; legislation; monopsony